Relationship Between Muscle Stiffness Derived from Fatigue and Estimated Muscle Mass (International Journal of Physiotherapy, 2024)
Background: This study aimed to investigate the relationship between muscle mass and the effect of contraction tasks leading to biceps fatigue on the joint drive resistance of the elbow joint.Methods: A total of 23 healthy men were included in this study. A muscle tone electromyograph was used to measure joint drive resistance in passive flexion and elbow joint extension before and after the muscle contraction task. The slope of the regression line of the angular torque during passive motion was calculated and analyzed as the elastic coefficient. We also investigated the relationship between the estimated muscle mass and the joint drive resistance.Results: Muscle contraction leading to biceps fatigue increases the elastic coefficient of the elbow joint. During muscle fatigue, a relationship was observed between the rate of change in the elastic modulus and the estimated muscle mass.Conclusion: The muscle contraction task leading to fatigue increases joint drive resistance, and the rate of increase is related to muscle mass.